The relationship between interest rate and stock market in Malaysia / Noorulasikin Mohd Noor - Mohd Noor, Noorulasikin (Faculty of Business and Management, 2013)
This study examines the relationships between interest rate and stock market in Malaysia and the relationships between interest rate and stock market in Malaysia in different economic condition. Extending related empirical studies, comparative analyses of pre-crisis, crisis, and post crisis periods are conducted to comprehensively evaluate how the relationship between interest rate and stock market in Malaysia was affected by financial crises. In general, the results show that no relationships between interest rate and stock market in Malaysia. In addition, Interest Rate has no significant relationship on stock market in Malaysia at pre-economic crisis and during economic crisis. However, interest rate has significant relationship with stock market at post economic crisis. In addition to this, interest rates are one of the macroeconomic variables that will explain stock market in Malaysia. In this paper Regression Analysis approach was used to determine the significant relationship between interest rate and stock market in Malaysia by way of analysing the trend of the interest rate and stock markets for the period January 2005 to August 2010. Monthly data were used for the analysis.